HUBUNGAN ANTARA MOTIVASI KERJA DAN KEDISIPLINAN DENGAN KOMPETENSI PROFESIONAL GURUDI MADRASAH ALIYAH MUALLIMIN UNIVA KECAMATAN MEDAN AMPLAS - Kholijah Nur Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This study aims to find out: (1) significant and meaningful relationship between work motivation and professional competence of teachers at Madrasah Aliyah Muallimin UNIVA Medan Amplas Subdistrict. (2) significant and meaningful relationship between teacher discipline and professional competence of teacher at Madrasah Aliyah Muallimin UNIVA Medan Subdistrict, (3) significant relationship And means between work motivation and discipline of teachers with professional competence of teachers at Madrasah Aliyah Muallimin UNIVA Medan Amplas District,This research uses quantitative research type of descriptive method correlational study. The population in this study were all Madrasah Aliyah Muallimin Univa Teachers of Medan Amplas in academic year 2016/2017. The total sample is 42 people.This can be seen from the large simple correlation between X1 and Y (rX1Y) = 0.379. These results were consulted with rtabel with N = 42 at significance level of 5% = 0.304. With rX1Y = 0.379 obtained t count = 2,586. These results were consulted with ttable with N = 42 at 5% significance level = 1.68. Then from the calculation results with partial correlation obtained ry, 2.1 = 0.376. These results were consulted with rtabel with N = 42 at significance level of 5% = 0.304. With ry, 2.1 = 0.376 obtained thitung = 2,531. These results were consulted with ttable with N = 42 at 5% significance level = 1.68.Also found there is a positive and meaningful relationship between discipline with professional competence of teachers. This can be seen from the large simple correlation between X2 with Y (rX2Y) = 0.374. These results were consulted with rtabel with N = 42 at significance level of 5% = 0.304. With the price rX2Y = 0.374 obtained tcount = 2.552. These results were consulted with ttable with N = 42 at 5% significance level = 1.68. Then from the calculation results with partial correlation obtained ry, 1.2 = 0.371. These results were consulted with rtabel with N = 42 at significance level of 5% = 0.304. With the price ry, 1.2 = 0.371 obtained tcount = 2.497. These results were consulted with ttable with N = 42 at 5% significance level = 1.68.In addition found a positive and meaningful relationship between work motivation and discipline with professional competence of teachers with correlation coefficient Ry (1,2) = 0,554; While rtabel with N = 42 and 5% significance level of 0,304. Thus the price Rhitung> rtabel (0,554> 0,304). Furthermore, the significance test of correlation by using F-test. With Rhitung = 0,554 obtained Fcount = 8,638. The price of Ftable for N = 42 at the 5% significance level is 3.23. Because Fcount> Ftable (8,638> 3,23).